Dalla diversità all'inclusione - Venuta, Fabrizia (Fuori collana, 2022)
Starting 2011, Fabrizia Venuta has developed projects of seasons of foreign language films addressed to schools, focused on specific topics also deepened with seminars. Students taking part in the projects have to make a final composition, that will be exhibited during a project's final event taking place at the University Federico II. The sixth season entitled "From Outside in", from which this book derived its title, took place from November 2019 until May 2020, had an enthusiastic students' attendance and emotional involvements reflected in the fairy tales, short stories, essays, lyrics and poems they wrote both in Italian and English. In this book all the literary works have been collected, ordered by genres and grouped in a first part in Italian and a second part in English. This book is an invitation to reflect on the path that can lead a teenager from a situation of initial exclusion to the integration in his/her own social context and on how the way in which they go through this process may help adults to better understand them and to became better human beings and parents.